1992
DOI: 10.1111/j.1365-2362.1992.tb01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetic studies of a human haemopoietic growth factor, GM‐CSF

Abstract: The pharmacokinetics of glycosylated recombinant human granulocyte-macrophage colony-stimulating factor (rhGM-CSF) was studied following intravenous (i.v.) and subcutaneous (s.c.) bolus injection of rhGM-CSF, 8 micrograms kg-1 employing a sensitive radioimmunoassay. After a single i.v. bolus injection, an initial high serum level of rhGM-CSF was observed, followed by a rapid decrease that occurred in two phases with a half-life (t1/2) alpha of 20.0 +/- 5 min and a t1/2 beta of 68.3 +/- 8 min. Following s.c. bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Moreover, some studies have suggested that hGM‐CSF lacking N‐linked carbohydrate has a significantly enhanced specific activity in vitro when compared to the native recombinant cytokine (2, 15). However, there are numerous evidences supporting the key role of carbohydrate chains in hGM‐CSF functions, such as pharmacokinetic, toxicity, and immunogenicity (16).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some studies have suggested that hGM‐CSF lacking N‐linked carbohydrate has a significantly enhanced specific activity in vitro when compared to the native recombinant cytokine (2, 15). However, there are numerous evidences supporting the key role of carbohydrate chains in hGM‐CSF functions, such as pharmacokinetic, toxicity, and immunogenicity (16).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous clinical trial, we demonstrated that replication could result in detectable GM-CSF in blood when other inflammatory cytokines had returned to baseline (days 4-15)[7], despite the relatively short half-life of GM-CSF (< 2h) [10]. Therefore, detection of GM-CSF in blood is indicative of high-level GM-CSF expression, and may be a specific but insensitive marker of transgene expression.…”
Section: Pharmacokinetics and Sheddingmentioning
confidence: 94%
“…Since the action of PNGase F results in the liberation of N-glycans and the simultaneous conversion of the asparagine to aspartic acid, previously glycosylated peptides exhibit a mass increase of 1 Da which can be easily detected by mass spectrometry. The ratio of unglycosylated to glycosylated GP I [LLN(D)LSR (25)(26)(27)(28)(29)(30)] was found to be approximately 40 : 60. For GP II [DT AAEMN(D)ETVEVISEMFDLQEPTCLQTR(31-58)], a ratio of approximately 15 : 85 of unglycosylated and N-glycosylated peptide form was determined.…”
Section: Site Specific Glycosylation Of Gm-csfmentioning
confidence: 99%